Interruption of pregnancy in México within the framework of human rights - Morga, Felipe César González (Technium Social Sciences Journal, 2024)
The Mexican State is part of the inter-American system, it safeguards the human rights of both the Political Constitution of the United Mexican States and the International Treaties, particularly in the interruption of pregnancy it protects the human rights to life, health, reproductive rights and non-discrimination. These human rights are analyzed in the resolutions of the Inter-American Court of Human Rights, the Inter-American Commission on Human Rights and the Supreme Court of Justice of the Nation, to aknowledge both the international and national interpretation, which has served as a legal basis in the interruption of pregnancy in Mexico. Based on these human rights and resolutions, ten states have legislated to allow the interruption of pregnancy, due to which the legal framework of the former Federal District (D.F.), Oaxaca, Hidalgo, Baja California, Veracruz, Colima, Sinaloa, Guerrero, Baja is studied. California Sur and Quintana Roo, highlighting that they have reformed their Penal Codes and Health Laws, standardizing most of their criteria. Likewise, a legal comparison is made at an international level to highlight differences and similarities between Mexico and other countries. This issue continues in Mexico, the states continue to discuss the interruption of pregnancy